Impact of corporate strategy on the digitalization of management control: evidence from Moroccan companies - El-Moumane, Rajae; Elhamma, Azzouz (European Scientific Journal, ESJ, 2024)
For several years, digitalization has become a significant and essential strategic issue for companies, affecting all their functions, including Human Resources Management (HRM), logistics, finance, etc. It is the subject of several research studies, especially in developed countries. Unfortunately, this type of work is still largely absent in developing countries. In this context, this paper, based on a survey conducted among forty-two companies in Morocco, attempts to answer two main questions. First, how can we assess the degree of digitalization of management control in these companies? Second, does corporate strategy have a significant impact on this digitalization? The main study results indicate that the level of digitalization can be classified as "moderate." Additionally, we have shown that strategy has a significant impact on the digitalization of management control; specifically, prospector companies adopt more digital management control systems than defender companies. This research work makes important contributions at both the theoretical and managerial levels.